Maimon and Cohen on differential calculus, transcendental philosophy and metaphysics - Pringe, Hernan Bruno (2024)
Salomon Maimon and Hermann Cohen propose a profound modification of Kantian philosophy through a transcendental interpretation of differential calculus. This paper presents both theories and discusses their implications for the possibility of metaphysics.